Strategi dalam Meningkatkan Pemahaman Dasar Bagi Peserta Didik di Desa Belawan Sicanang - Mayzura M; Isman Efendi Limbong (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to identify effective strategies for improving the basic understanding of students in Belawan Sicanang Village. The background of this research stems from the low level of students’ basic comprehension of learning materials, influenced by environmental factors, limited learning facilities, and the lack of varied teaching methods applied by educators. This study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings reveal that the implementation of active learning strategies such as discussion methods, demonstrations, and simple project-based learning effectively enhances students’ engagement and understanding. Moreover, collaboration among teachers, parents, and the local community plays a crucial role in creating a supportive learning environment. The study concludes that improving students’ basic understanding in Belawan Sicanang Village can be achieved through contextual, participatory, and locally adapted learning strategies.